PENGARUH WAKTU APLIKASI OKULASI TERHADAP KEBERHASILAN PERTUMBUHAN OKULASI BIBIT KARET (Hevea brasilliensis Muell Erg.) - Anwar, Risvan; Mulatsih, Sri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2014)
The  study  aims  to  determine  the  time  of  grafting  seedlings  rubber  tree  (hevea brasiliensis Muell Erg.) Which consists of a morning, afternoon and evening on success of grafting growth. The experiment was conducted in village of Taba Tembilang Arga Makmur  district  of  North  Bengkulu,  in  September  until  November  2012.  The experiment was conducted using a randomized Completely Block Design (RCBD) with a single factor, namely time of application grafting with replay 4 times. Factors studied were time applications grafting (W) is: W1 = In the morning hours of 07:00 to 08,00, afternoon   W2 = 13.00 -14.00, and evening   17.00-18.00. The study concluded that: (Time) does not affect the application of grafting significantly to the success of grafting and shoots of growth, (2) No application time best rubber grafted seedlings. Application of rubber seedling grafting can be done anytime.